Bioreducible nanocapsules for folic acid-assisted targeting and effective tumor-specific chemotherapy - Yi Q (Dove Medical Press, 2018)
Qiangying Yi,1 Jin Ma,1 Ke Kang,1 Zhongwei Gu1,2 1National Engineering Research Center for Biomaterials, Sichuan University, Chengdu, 2College of Materials Science and Engineering, Nanjing Tech University, Nanjing, P.R. China Introduction: Increasing demands in precise control over delivery and functionalization of therapeutic agents for tumor-specific chemotherapy have led to a rapid development in nanocarriers. Herein, we report a nanocapsule (NC) system for tumor-oriented drug delivery and effective tumor therapy.Materials and methods: Functionalized hyaluronan is utilized to build up the NC shells, in which bioreduction cleavable sites, targeting ligand folic acid (FA), and zwitterionic tentacles are integrated.Results: The hollow NCs obtained (~50 nm in diameter) showed well-defined spherical shell structures with a shell thickness of ~8 nm. These specially designed NCs (doxorubicin [DOX]/FA-Z-NCs) with high drug encapsulation content exhibited good biocompatibility in vitro and fast intracellular drug release behavior mediated by intracellular glutathione.Conclusion: Cellular uptake tests demonstrated rapid uptake of these functionalized NCs and effective escape from endosomes. Antitumor efficacy of the DOX/FA-Z-NCs was confirmed by the significant tumor growth inhibition effect as well as greatly reduced side effects, in contrast with those of the free drug DOX hydrochloride. Keywords: drug delivery, active targeting, zwitterionic poly(carboxybetaine methacrylate), doxorubicin